Artes indígenas e a escola não indígena: a retomada da cultura entre os Pataxó e os Xakriabá - Tales Bedeschi Faria (2020)
The thesis "Indigenous arts and the non-indigenous school: the repossession of culture among the Pataxó and the Xakriabá" aims to develop methodological approaches capable of working the cultural and, above all, artistic universe of indigenous peoples as the Pataxó and the Xakriabá with authenticity, scientific bias and respect for the cultures involved. To this end, it undertakes a path of coexistence and learning of the traditional and school education of the Pataxó People, considering that a culture distinct from monoepistemic school culture can only be understood through methodological approaches that are suitable for it. Supported by Law No. 11,645 / 2008, which establishes the obligation to teach the history and culture of indigenous peoples, the thesis meets the ‘how’: how can the teacher teach a culture he has never learned? Based on the assertions of indigenous thinkers (Arissana Pataxó, Célia and Nei Xakriabá, Gersem Baniwa, Dona Liça Pataxoop, Tyson Yunkaporta) and non-indigenous thinkers (Ana Mae Barbosa, Eduardo Viveiros de Castro, Paulo Freire), it elaborates pedagogical experiences based on ideas such as ‘researching together’, ‘planting pataxó’s concepts’, ‘epistemological oppression’, ‘relearning to learn’, which aim to guide the teacher to teach and learn the art of a culture that has a epistemological basis other than that usually present in schools. The proposal is to trace an investigative trajectory that allows the teacher to overcome the conventional indigenization of of the contents, in favor of an experimentation of pataxós’s concepts and processes in the school curriculum.